Manoj Basur Koyekti Chhotogalpo : Deshbhag, Sampradayik Danga O Hindu-Musalman Somporker Antorboyan/ মনোজ বসুর কয়েকটি ছোটগল্প : দেশভাগ, সাম্প্রদায়িক দাঙ্গা ও হিন্দু-মুসলমান সম্পর্কের অন্তর্বয়ান (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
The forties are very significant in Bengali literature. The partition, riots and the crisis of refuges life are reflected in every form of literature. The impact of partition and ritos is reflected a little more in the stories. The brutality of the riots, violence and hatred, and the pain of partition have been reflected in the writings of many story taller’s. Manoj Basu is one of the few storytellers who embodied the riots and partition in the pens of the fortis and fifties. Compassion for the homeland and relatives, that is, the people, is the main feature of Manoj Basu's literature. Just as there is a thorough picture of how public life was disrupted in the Hindu-Muslim riots and the partition after independence. Manoj Basu's stories also show the picture of people coming together, forgetting the memories of the riots and partition. The riots created districts between the two Nations, Hindus and Muslims, and partition increased it. Therefor after partition, communal classes and unrest increased even more. storyteller Manoj Basu has sympathetically portrayed the people in danger during riots and partition in his stories after independence. And so we see the harmony of Hindu-Muslim relations in his stories. He believed that oneday all the darkness would pass, the storm would stop and light would shine again, all the unrest would end. That is why he has faith in people and he wanted to protray that in his stories. In stories like 'Hindu Muslim Danga', ‘Dangar Ekti Kahini', ‘Dangar Daag', ‘Hindu Muslim’, ‘Simanta', ‘Epar Opar', ‘Tanter Maku' etc. The author has protrayed the picture of Hindu Muslim relations during the riots and partitions during the contemporary and post partition period with experience. His stories have become an intertextual account of Hindu Muslim relations. Manoj Basu wanted to show the good heart of a person can never die. Even if riots and partition temporary separate people, it can never be permanent. When the fire of hatred and jealousy dies down, faith in each other returns because people always stand by each other losing faith in people is a sin— this message of hope is echoed in Manoj Basu's stories.
Keywords: Partition; Communal Riot; Refugee; Hindu; Muslim; Faith; Humanism; Communal Harmony